Simulation-Based Nursing Education in Improving Clinical Competence - Partono Siswosuharjo; Hardjito S. Darmojo; Fathiyati Fathiyati (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
Nursing education is required to produce graduates with adequate clinical competency to ensure the quality and safety of healthcare services. One rapidly developing innovative learning approach is simulation-based nursing education, designed to bridge the gap between theory and clinical practice. This study aimed to analyze the effect of simulation-based nursing education on improving the clinical competency of nursing students. The study used a quasi-experimental design with a pretest-posttest approach and a control group. The study sample consisted of 80 nursing students divided into an intervention group and a control group. The intervention group received simulation-based clinical learning, while the control group underwent conventional clinical learning. Clinical competency was measured using the Objective Structured Clinical Examination (OSCE) and a standardized clinical skills instrument. Data analysis was performed using paired t-tests and independent t-tests. The results showed a significant increase in clinical competency in the intervention group compared to the control group (p < 0.001) with a strong effect size. These findings indicate that simulation-based nursing education is effective in improving clinical skills, decision-making, and student confidence. Therefore, simulation is recommended as a primary learning strategy in nursing education to enhance graduates' clinical readiness